A ZIF-67 derived Co@C / RGO double-layer microwave absorbing film and its preparation method and application
By preparing the ZIF-67 derivative of CO@C/RGO double-layer suction film, use graphene to adsorb ZIF-67 and perform high temperature treatment, solve the problem of the ZIF-67 difficult to form a thin film, and achieve wide bandwidth absorption performance. Effective bandwidth is 13.6GHz.
Patent Information
- Application Number
- CN202211011427.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2042-08-23
AI Technical Summary
In the prior art, ZIF-67 is difficult to form a uniform thin film material due to strong electrostatic effects, and the electromagnetic wave absorption performance of the existing wave absorbing materials is insufficient and the effective bandwidth is not wide enough.
By preparing ZIF-67 derivative CO@C/RGO double-layer suction film, the negative electrical adsorption ZIF-67 of graphene is used to form a double-layer film and optimize the material structure through high temperature treatment to improve the suction performance.
It has achieved simply preparation of lightweight and flexible ZIF-67/GO double-layer film at normal temperature, and the ZIF-67 derivative of the ZIF-67 derivative of the ZIF-67 is obtained by high temperature treatment. Within 2-18GHz, the effective bandwidth of more than 90%of the electromagnetic wave absorption rate can reach 13.6GHz.
Smart Images

Figure CN115379752B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of electromagnetic wave absorbing materials, and specifically relates to a ZIF-67 derived Co@C / RGO double-layer absorbing film and a preparation method and application thereof. Background Art
[0002] With the rapid development of electronic information technology, electromagnetic pollution will not only interfere with electromagnetic control systems, but also endanger human health. Therefore, it is of great significance to develop efficient electromagnetic wave absorbing materials. The microwave frequency range of absorbing materials is mainly 2-18GHz. In this frequency range, the electromagnetic wave absorption rate reaches more than 90%, that is, the frequency range with reflection loss less than -10 is called effective bandwidth.
[0003] Currently, electromagnetic wave absorbing materials derived from magnetic metal cobalt derived from the metal organic framework ZIF-67 and compounded with other dielectric materials are a hot topic. Researchers compounded it with dielectric materials and regulated the comprehensive electromagnetic parameters of the material, thereby optimizing its wave absorption and energy absorption and increasing its effective bandwidth.
[0004] Chinese invention patent CN112030135A discloses a method for preparing a highly efficient composite absorbing material ZIF-67@CNTs. The powder material has good absorbing properties, but its effective bandwidth is not good enough and can only cover the X-band, which is 5.78GHz.
[0005] Chinese invention patent CN110283569A discloses a method for preparing a composite absorbing material of Ni-Co alloy inlaid N-doped graphite carbon capsules. ZIF-67 is synthesized in a relatively common way, and a composite absorbing material powder is prepared. The maximum effective bandwidth is about 6.5 GHz. However, the prepared material is a powder, and its mechanical properties before heat treatment are relatively poor compared to those of thin film materials. The ZIF-67 material itself has strong electrostatic effects and is difficult to form a uniform thin film material, which also limits its further application. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies in the prior art, provide a ZIF-67 derived Co@C / RGO double-layer absorbing film and its preparation method and application, solve the problem that ZIF-67 is difficult to form a uniform film due to strong electrostatic repulsion, and improve the electromagnetic wave absorption performance of existing absorbing materials.
[0007] The present invention provides the following technical solutions:
[0008] In a first aspect, a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film is provided, comprising the following steps:
[0009] Adding cobalt nitrate hexahydrate, 2-methylimidazole and polyvinyl pyrrolidone into methanol, stirring and aging to obtain an aging liquid;
[0010] The copper chloride and graphite oxide sol are added into methanol and dispersed by ultrasonication to obtain a graphene oxide dispersion;
[0011] Adding the graphene oxide dispersion into the aging solution and stirring to obtain a mixed solution;
[0012] The mixed solution is filtered to obtain a filtration membrane with a 2-methylimidazole cobalt / graphene oxide double-layer membrane (ZIF-67 / GO double-layer membrane) attached thereto, and dried to obtain a dried ZIF-67 / GO double-layer membrane;
[0013] The dried ZIF-67 / GO double-layer film was treated at high temperature to obtain the ZIF-67 derived Co@C / RGO double-layer absorbing film.
[0014] Furthermore, the mass ratio of the cobalt nitrate hexahydrate to 2-methylimidazole is 1:2-1:6, and the mass ratio of the cobalt nitrate hexahydrate to polyvinyl pyrrolidone is 1:0.5-1:2.
[0015] Furthermore, the stirring time after adding methanol to the cobalt nitrate hexahydrate, 2-methylimidazole and polyvinyl pyrrolidone is 40-80 minutes, and the aging time is 4-8 hours. The aging process is the growth process of the metal organic framework ZIF-67. If the aging time is too short, the generated ZIF-67 is too little and too small. If the aging time is too long, it will completely grow into a rhombic dodecahedron structure, resulting in excessively high conductivity after the final pyrolysis, which ultimately inhibits the material from absorbing waves and energy.
[0016] Furthermore, the mass ratio of the copper chloride and graphite oxide in the graphite oxide sol is 1:0.5-1:2, and the ultrasonic dispersion time is 20-40 min; the concentration of graphene oxide in the graphene oxide dispersion is 0.5-5 mg / mL. If the concentration is too low, the yield is low, resulting in a large amount of waste, and if the concentration is too high, the ultrasonic dispersion cannot be uniformly dispersed.
[0017] Furthermore, the volume ratio of the graphene oxide dispersion and the aging liquid is 5:1; after the graphene oxide dispersion is added to the aging liquid, magnetic stirring is performed at a stirring rate of 400-600 r / min and a stirring time of 5-30 min. The vigorous stirring method can fully physically mix the graphene oxide dispersion and the aging liquid, and at the same time, the graphene oxide and the ZIF-67 generated by the aging liquid are combined to a certain extent.
[0018] Furthermore, the specific method for filtering the mixed liquid is: placing a filtration membrane on the sand core of a filtration bottle, setting up a filtration device, pouring 5-40 mL of the mixed liquid into the filtration device for filtration, and the filtration time is 5-20 min; the filtration membrane is a polyvinylidene fluoride filter membrane or a polytetrafluoroethylene filter membrane, and the pore size of the filtration membrane is 220-1000 nm.
[0019] Furthermore, the filtration membrane with the ZIF-67 / GO double-layer membrane attached is dried in air for 5-20 minutes. After drying, the edge of the filtration membrane is slightly bent, and the dried ZIF-67 / GO double-layer membrane will gradually fall off from the edge naturally.
[0020] Furthermore, the temperature of the dried ZIF-67 / GO double-layer membrane for high temperature treatment is 300-900°C, and the insulation time is 2-4 hours. If the treatment temperature is too low, ZIF-67 is difficult to be pyrolyzed into cobalt and carbon that are beneficial to wave absorption, while if the temperature is too high, the sample will be broken and it will be difficult to obtain a complete membrane.
[0021] In the second aspect, a ZIF-67-derived Co@C / RGO double-layer absorbing film obtained by the preparation method described in the first aspect is provided.
[0022] In a third aspect, a ZIF-67-derived Co@C / RGO double-layer absorbing film obtained by the preparation method described in the first aspect is provided for use in electromagnetic wave absorption.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The surface of ZIF-67 particles often carries a positive charge. Due to electrostatic attraction, the particles repel each other, and pure ZIF-67 particles are difficult to form a film. However, the surface of the two-dimensional material graphene oxide is usually negatively charged and can adsorb ZIF-67 to form a film. Therefore, the preparation method provided by the present invention can simply prepare a lightweight and flexible ZIF-67 / GO double-layer film at room temperature in air, solving the problem that ZIF-67 is difficult to form a uniform film due to strong electrostatic attraction and mutual repulsion;
[0025] (2) The present invention obtains a ZIF-67-derived Co@C / RGO double-layer absorbing film by subjecting a ZIF-67 / GO double-layer membrane to high-temperature treatment. The Co@C layer has good impedance matching capability and can effectively introduce electromagnetic waves into the interior of the film. The RGO layer also has good absorbing performance. The overall structural design expands the effective absorbing bandwidth of the pure carbon material, so that the finally obtained ZIF-67-derived Co@C / RGO double-layer absorbing film has good comprehensive absorbing performance. In the range of 2-18 GHz, the effective bandwidth with an electromagnetic wave absorption rate exceeding 90% can reach 13.6 GHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is the appearance of the ZIF-67 / GO double-layer membrane in Example 1 of the present invention, (a) GO is the main surface, (b) ZIF-67 is the main surface;
[0027] Figure 2 is the reflection loss of the double-layer absorbing film in Example 1 in the range of 2-18 GHz;
[0028] Figure 3 is the reflection loss of the double-layer absorbing film in Example 2 in the range of 2-18 GHz;
[0029] Figure 4 is the reflection loss of the double-layer absorbing film in Example 3 in the range of 2-18 GHz;
[0030] Figure 5 is the reflection loss of the double-layer absorbing film in Example 4 in the range of 2-18 GHz;
[0031] Figure 6 is the reflection loss of the double-layer absorbing film in Example 5 in the range of 2-18 GHz. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.
[0033] Example 1
[0034] This embodiment provides a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, comprising the following steps:
[0035] Step 1: Add 160 mg of cobalt nitrate hexahydrate, 640 mg of 2-methylimidazole and 160 mg of polyvinyl pyrrolidone into 20 ml of methanol, stir for 1 hour and then age for 5 hours to obtain an aged solution.
[0036] Step 2: 100 mg of copper chloride and 10 mL of graphite oxide sol with a concentration of 10 mg / mL are added to 100 mL of methanol, and ultrasonic dispersion is performed for 30 min to uniformly disperse the graphene oxide in the methanol to obtain a graphene oxide dispersion.
[0037] Step 3, adding the graphene oxide dispersion of step (2) to the aged solution of step (1), and vigorously stirring at a rate of 500 r / min for 10 min by means of magnetic stirring to obtain a mixed solution;
[0038] Step 4: Place a polyvinylidene fluoride filtration membrane with a pore size of 220 nm on the sand core of the filtration bottle, set up the filtration device, take 20 mL of the mixed solution in step (3) and pour it into the filtration device for filtration. After 10 minutes, the filtration membrane with the ZIF-67 / GO double-layer membrane attached is removed. Figure 1 As shown, the ZIF-67 / GO bilayer membrane is soft as a whole and can be folded multiple times. Figure 1 (a) is the graphene oxide-based side, which is gray-black in color. Figure 1 (b) is the other side mainly composed of ZIF-67, which is dark purple in color (due to the requirement that the drawings in the specification cannot be colored, Figure 1 After grayscale treatment, both sides appear gray-black).
[0039] Step 5: Dry the filtration membrane with the ZIF-67 / GO double-layer membrane attached in step (4) in air for 15 min to obtain a dried ZIF-67 / GO double-layer membrane.
[0040] Step 6: Slightly bend the edge of the filtration membrane in step (5), and the dried ZIF-67 / GO double-layer membrane will gradually fall off from the edge naturally.
[0041] Step 7: Heat treat the dried ZIF-67 / GO double-layer film at 400°C for 3 h to obtain a ZIF-67-derived Co@C / RGO double-layer absorbing film.
[0042] Example 2
[0043] This embodiment provides a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, which is different from Example 1 in that in step 7, the dried ZIF-67 / GO double-layer film is heat-treated at 500°C for 3 hours to obtain a ZIF-67 derived Co@C / RGO double-layer absorbing film.
[0044] Example 3
[0045] This embodiment provides a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, which is different from Example 1 in that in step 7, the dried ZIF-67 / GO double-layer film is heat-treated at 600°C for 3 hours to obtain a ZIF-67 derived Co@C / RGO double-layer absorbing film.
[0046] Example 4
[0047] This embodiment provides a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, which is different from Example 1 in that in step 7, the dried ZIF-67 / GO double-layer film is heat-treated at 700°C for 3 hours to obtain a ZIF-67 derived Co@C / RGO double-layer absorbing film.
[0048] Example 5
[0049] This embodiment provides a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, which is different from Example 1 in that in step 7, the dried ZIF-67 / GO double-layer film is heat-treated at 800°C for 3 hours to obtain a ZIF-67 derived Co@C / RGO double-layer absorbing film.
[0050] Example 6
[0051] This embodiment provides a method for preparing a ZIF-67-derived Co@C / RGO double-layer absorbing film, which is different from that of Example 1 in that, in step 4, a polytetrafluoroethylene suction filter membrane with a pore size of 450 nm is placed on the sand core of a suction filter bottle, a suction filter device is set up, 20 mL of the mixed solution in step 3 is poured into the suction filter device for suction filtration, and the suction filtration is completed after 15 minutes, and the suction filter membrane attached with the ZIF-67 / GO double-layer membrane is removed. The finally obtained ZIF-67-derived Co@C / RGO double-layer absorbing film is not significantly different from that of Example 1.
[0052] Example 7
[0053] This embodiment provides a method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, comprising the following steps:
[0054] Step 1: Add 160 mg of cobalt nitrate hexahydrate, 320 mg of 2-methylimidazole and 80 mg of polyvinyl pyrrolidone to 20 mL of methanol, stir for 40 min and age for 4 h to obtain an aged solution.
[0055] Step 2: 100 mg of copper chloride and 5 mL of graphite oxide sol with a concentration of 10 mg / mL are added to 100 mL of methanol, and ultrasonic dispersion is performed for 20 min to uniformly disperse the graphene oxide in the methanol to obtain a graphene oxide dispersion.
[0056] Step 3, adding the graphene oxide dispersion of step (2) to the aged solution of step (1), and vigorously stirring at a rate of 600 r / min for 10 min by means of magnetic stirring to obtain a mixed solution;
[0057] Step 4: Place a polyvinylidene fluoride filtration membrane with a pore size of 450 nm on the sand core of the filtration bottle, set up the filtration device, take 40 mL of the mixed solution in step (3) and pour it into the filtration device for filtration. After 20 minutes, the filtration membrane with the ZIF-67 / GO double-layer membrane attached is removed.
[0058] Step 5: Dry the filtration membrane with the ZIF-67 / GO double-layer membrane attached in step (4) in air for 20 min to obtain a dried ZIF-67 / GO double-layer membrane.
[0059] Step 6: Slightly bend the edge of the filtration membrane in step (5), and the dried ZIF-67 / GO double-layer membrane will gradually fall off from the edge naturally.
[0060] Step 7: Heat treat the dried ZIF-67 / GO double-layer film at 900°C for 3 h to obtain a ZIF-67-derived Co@C / RGO double-layer absorbing film.
[0061] Example 8
[0062] Step 1: Add 160 mg of cobalt nitrate hexahydrate, 960 mg of 2-methylimidazole and 320 mg of polyvinyl pyrrolidone to 20 mL of methanol, stir for 80 min and age for 8 h to obtain an aged solution.
[0063] Step 2: 100 mg of copper chloride and 20 mL of graphite oxide sol with a concentration of 10 mg / mL are added to 100 mL of methanol, and ultrasonic dispersion is performed for 40 min to uniformly disperse graphene oxide in methanol to obtain a graphene oxide dispersion.
[0064] Step 3, adding the graphene oxide dispersion of step (2) to the aged solution of step (1), and vigorously stirring at a rate of 400 r / min for 10 min by means of magnetic stirring to obtain a mixed solution;
[0065] Step 4: Place a polytetrafluoroethylene filtration membrane with a pore size of 1000 nm on the sand core of the filtration bottle, set up the filtration device, take 5 mL of the mixed solution in step (3) and pour it into the filtration device for filtration. After 5 minutes, the filtration is completed and the filtration membrane with the ZIF-67 / GO double-layer membrane attached is removed.
[0066] Step 5: Dry the filtration membrane with the ZIF-67 / GO double-layer membrane attached in step (4) in air for 5 min to obtain a dried ZIF-67 / GO double-layer membrane.
[0067] Step 6: Slightly bend the edge of the filtration membrane in step (5), and the dried ZIF-67 / GO double-layer membrane will gradually fall off from the edge naturally.
[0068] Step 7: Heat treat the dried ZIF-67 / GO double-layer film at 300°C for 3h to obtain a ZIF-67-derived Co@C / RGO double-layer absorbing film.
[0069] Comparative Example 1
[0070] Step 1, step 2 and step 3 of this comparative example are the same as step 1, step 2 and step 3 in embodiment 1.
[0071] Step 4: Place a nylon filtration membrane with a pore size of 2000 nm on the sand core of the filtration bottle, set up the filtration device, pour the mixed solution in step 3 into the filtration device, and start filtration. The filtrate permeates out of the filter membrane and cannot form a uniform film.
[0072] Comparative Example 2
[0073] Step 1 is the same as step 1 in Example 1.
[0074] Step 2: Add 10 mL of graphite oxide sol with a concentration of 10 mg / mL into 100 mL of methanol, and perform ultrasonic dispersion for 30 minutes to uniformly disperse the graphene oxide in the methanol.
[0075] Step 3 is the same as step 3 in Example 1.
[0076] Step 4: Place a polyvinylidene fluoride filtration membrane with a pore size of 220 nm on the sand core of the filtration bottle, set up the filtration device, pour the mixed solution in step 3 into the filtration device, and the filtrate cannot be effectively extracted.
[0077] Performance comparison
[0078] 1. By comparing Example 1, Example 6, Comparative Example 1 and Comparative Example 2, it can be observed that: (1) the material of the filter membrane itself has no obvious effect on the product, but the pore size of the filter membrane is too large, which will result in the inability to separate the solid and the solution, and thus the required film cannot be formed; (2) Failure to add copper chloride will also result in too low a suction filtration efficiency, making it impossible to carry out the preparation process. This is because the adsorption effect of graphene oxide adsorbs copper ions on the surface of graphene oxide, separating the graphene layers, leaving the gaps required for suction filtration. Without adding copper chloride, the graphene layers are stacked, and after a short period of suction filtration, a dense layer similar to a layer is formed to block the suction pores.
[0079] 2. The ZIF-67-derived Co@C / RGO double-layer absorbing films prepared in Examples 1-5 were used to test the electromagnetic wave absorption performance. The reflection loss of each double-layer absorbing film in the range of 2-18 GHz is as follows: Figure 2-6 shown.
[0080] For absorbing materials, the frequency range in which the reflection loss is less than -10dB, that is, the effective bandwidth, can best reflect the absorbing performance and application range of the material; within the range of 2-18GHz, the wider the effective bandwidth, the better the absorbing performance, and the more conducive it is to future use and promotion. Figure 2-6 It shows that the materials in each embodiment have good wave absorbing performance. Figure 4The representative embodiment 3 has a bandwidth in the range of 4.4-18 GHz, which almost covers the vast majority of 2-18 GHz in the research field. Compared with other embodiments, embodiment 3 has the widest bandwidth, indicating that embodiment 3 has the best wave absorption performance and the largest effective bandwidth, reaching 13.6 GHz, compared with the other four embodiments, and can effectively absorb electromagnetic waves in the range of 4.4-18 GHz. This has obvious advantages compared with other existing ZIF-67 derived cobalt / carbon composite materials, especially thin film materials that are difficult to prepare.
[0081] When the reflection loss is -10dB, it means that the electromagnetic wave is absorbed by 90%, when the reflection loss is -20dB, it means that the electromagnetic wave is absorbed by 99%, and so on. Therefore, the lowest reflection loss of the absorbing material indicates the most effective absorption capacity that the material can achieve at the most effective frequency. Figure 2-6 It shows that the materials in each embodiment have better reflection loss values. Figure 6 The reflection loss of the representative embodiment 5 is as low as -40 dB. Compared with other embodiments, the reflection loss value of embodiment 5 is the best.
[0082] 3. Compare Example 1 with Examples 7 and 8: The ZIF-67-derived Co@C / RGO double-layer absorbing film prepared in Example 1 has an appropriate thickness and good flexibility, while the ZIF-67-derived Co@C / RGO double-layer absorbing film prepared in Example 7 is fragile and easily broken; in Example 1, ZIF-67 is fully pyrolyzed, and the magnetic metal particles cobalt are obvious, while in Example 8, ZIF-67 is not fully pyrolyzed, and the magnetic metal particles cobalt are less obvious than in Example 1. The above results show that when some experimental parameters reach the end value of the range, the overall quality of the final film is greatly affected. Therefore, implementation outside the parameter range of the present invention should be avoided to avoid the situation of poor film performance and film formation difficulties.
[0083] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a ZIF-67 derived Co@C / RGO double-layer absorbing film, characterized in that: The following steps are involved: Adding cobalt nitrate hexahydrate, 2-methylimidazole and polyvinyl pyrrolidone into methanol, wherein the mass ratio of the cobalt nitrate hexahydrate to the 2-methylimidazole is 1:2-1:6, and the mass ratio of the cobalt nitrate hexahydrate to the polyvinyl pyrrolidone is 1:0.5-1:2, stirring and aging to obtain an aging liquid, the stirring time is 40-80 minutes, and the aging time is 4-8 hours; adding copper chloride and graphite oxide sol into methanol, wherein the mass ratio of graphite oxide in the copper chloride and graphite oxide sol is 1:0.5-1:2, and performing ultrasonic dispersion to obtain a graphene oxide dispersion; Adding the graphene oxide dispersion to the aging liquid, wherein the volume ratio of the graphene oxide dispersion to the aging liquid is 5:1, and stirring to obtain a mixed liquid; The mixed solution is filtered to obtain a filtration membrane with a ZIF-67 / GO double-layer membrane attached thereto, and dried to obtain a dried ZIF-67 / GO double-layer membrane; The dried ZIF-67 / GO double-layer film was treated at high temperature to obtain the ZIF-67 derived Co@C / RGO double-layer absorbing film.
2. The method for preparing the ZIF-67 derived Co@C / RGO double-layer absorbing film according to claim 1, characterized in that: The ultrasonic dispersion time is 20-40 min, and the concentration of graphene oxide in the graphene oxide dispersion is 0.5-5 mg / mL.
3. The method for preparing the ZIF-67 derived Co@C / RGO double-layer absorbing film according to claim 1, characterized in that: After the graphene oxide dispersion is added into the aging liquid, it is magnetically stirred at a stirring rate of 400-600 r / min and a stirring time of 5-30 min.
4. The method for preparing the ZIF-67 derived Co@C / RGO double-layer absorbing film according to claim 1, characterized in that: The specific method for filtering the mixed liquid is: placing a filtration membrane on the sand core of a filtration bottle, setting up a filtration device, pouring 5-40 mL of the mixed liquid into the filtration device for filtration, and the filtration time is 5-20 minutes; the filtration membrane is a polyvinylidene fluoride filter membrane or a polytetrafluoroethylene filter membrane, and the pore size of the filtration membrane is 220-1000 nm.
5. The method for preparing the ZIF-67 derived Co@C / RGO double-layer absorbing film according to claim 1, characterized in that: The filtration membrane with the ZIF-67 / GO double-layer membrane attached is dried in air for 5-20 minutes. After drying, the edge of the filtration membrane is slightly bent, and the dried ZIF-67 / GO double-layer membrane will gradually fall off from the edge naturally.
6. The method for preparing the ZIF-67 derived Co@C / RGO double-layer absorbing film according to claim 1, characterized in that: The temperature of high temperature treatment of the dried ZIF-67 / GO double-layer membrane is 300-900°C, and the insulation time is 2-4h.
7. A ZIF-67 derived Co@C / RGO double-layer absorbing film obtained by the preparation method according to any one of claims 1 to 6.
8. Application of a ZIF-67 derived Co@C / RGO double-layer absorbing film obtained by the preparation method according to any one of claims 1 to 6 in electromagnetic wave absorption.
Citation Information
Patent Citations
Preparation method of Ni-Co alloy embedded N-doped graphite carbon capsule composite wave-absorbing material
CN110283569A
Preparation method of efficient composite wave-absorbing material ZIF-67atCNTs
CN112030135A
Preparation method of ZIF-67 having multi-level pore structure, and honeycomb-like carbon / cobalt wave-absorbing material preparation method
CN109293939A
Graphene-based carbon-coated ZIF-67 derived cobalt oxide composite material and preparation method and application thereof
CN111162264A
Light and flexible wave-absorbing film and preparation method thereof
CN113629405A